The sensitive mobility of Cr in ashes studied by SiO2–Al2O3–Fe2O3–CaO system. (15th March 2023) - Yang, Zhe; Ning, Yu; Wang, Changxiang; Yang, Sen; Zhang, Wei; Dähn, Rainer; Li, Yilian
Abstract: Since incineration is a feasible method for stabilization/solidification of chromium (Cr)-enriched wastes, the species, distribution, and mobility of Cr in ashes deserve more studies, especially as the function of ash composition. Synthetic Cr-bearing ashes (SAs) were synthesized by SiO2 –Al2 O3 –Fe2 O3 –CaO systems to investigate Cr mobility under 1100 °C. A study from simplicity to complexity. The Cr in SiO2 –CaO is of high mobility with CrO4 2− formation, in contrary to the moderate mobility in SiO2 –Al2 O3 and poor mobility in SiO2 –Fe2 O3 . However, species and mobility of Cr are affected by the values of CaO/SiO2, Al2 O3 /SiO2, and Fe2 O3 /SiO2 ratios. When other oxides are added to the two-phase systems above, the fate of Cr is affected more considerably. With the SiO2 content of 70%, adding a slight amount of CaO (<10%) strengthens the stabilization/solidification of Cr, due to the favorable solid integration under Ca 2+ fusion. However, the Cr mobility is higher with increasing the CaO content further. The minimum content of CaO is ∼20% to sufficiently decrease the proportion of residual Cr (QCr-S5) in SiO2 –Al2 O3 –CaO, much lower than in SiO2 –Fe2 O3 –CaO, which confirms the easier release of Cr immobilized in Si–Al matrixes. Considering the opposite effects of Fe2 O3 and CaO on Cr mobility, increasing Fe2 O3 /CaO ratios >3/2 can limit the effect of CaO, leading to the efficient stabilization/solidification of Cr waste. Additionally, the QCr-S5 is 83% with the Fe2 O3 content of 15% in SiO2 –Al2 O3 –Fe2 O3, higher than in SiO2 –Al2 O3 and SiO2 –Fe2 O3 . This suggests the intense stabilization/solidification of Cr, probably due to the formation of amorphous Fe-rich glass. Based on these above, an equation is developed to describe the relationship between ash compositions and QCr-S5 (QCr-S5 = −39.37X1 + 24.96X2 + 5.34X3 – 2.51X4 + 54.29). Graphical abstract: Image 1 Highlights: Slight amounts of CaO (<10%) strengthen the stabilization/solidification of Cr. The release of Cr–S5 in SiO2 –Al2 O3 is easier than in SiO2 –Fe2O3 by Ca 2+ activation. The existence of Al2 O3 reduces Fe2 O3 content (15%) which makes a stabilized QCr-S5. An equation depicts the relationship between ash composition and QCr-S5 (R 2 = 82.6%).